Generating Public Engagement to Control Protests: State-managed Vigilantism in Poland - Rak, Joanna (Javnost-The Public, 2023)
Based on the expanded theory of soft repression and a qualitative news frame analysis, the article traces the dynamics of the mobilisation of non-violent means to block the All-Poland Women's Strike and decrease the cost of hard repression. It unpacks two aspects of generating negative public engagement in controlling protests: the public media's use of ridicule, stigma, and silencing and calls for countermovement violence and legitimising it. The main argument is that the Polish public media used interpretative frames characteristic of soft repression to challenge the movement and determine what ordinary people could do to contain threats to the government and regime stability resulting from protests. The new empirical approach reveals the non-obvious function of soft repression acting as an incitement tool for mobilising opponents of protesters under repression to steer dissent. By going beyond traditional illegitimating and demobilising functions of soft repression, the study provides an in-depth examination of the public media's endeavours to neutralise threats to the government and stabilise the Polish political system. Integrating the theory of soft repression and negative public engagement, the study advances an explanation of a managed change in the model of protest policing, which is making vigilantes the agents of protest control.